Revisiting the Australian Government's Growth Centres programme 1972–1975. (3rd September 2021) - Bolleter, Julian; Freestone, Robert; Cameron, Robert; Wilkinson, George; Hooper, Paula
ABSTRACT: From 1973 to 1975 a new Australian Government led by Gough Whitlam actively pursued plans to develop regional and sub-metropolitan Growth Centres with significantly boosted populations following a national strategy published in June 1973 which mapped a national coverage of prospective locations. The intention was for these centres to alleviate pressure on the capital cities considered overcrowded and deteriorating in efficiency and quality of life. The controversial dismissal of the Whitlam Government in 1975 signalled the winding back and effective demise of the programme. This paper examines the population projections for the centres under official consideration to 2000 and their actual growth. Despite the criticisms attached to this programme, several centres came close to achieving their population targets for 2000. Moreover, if Federal Government support had been sustained, more may have exceeded their projections. The implications for a resurgent national settlement policy are considered.